Analysis of Regional Interaction Patterns Suburbs of Medan City (Case Study: Sunggal District, Deli Serdang Regency) - Nur Ayu Ramadhani; Sirojuzilam Sirojuzilam; Agus Purwoko (Budapest International Research and Critics University, 2021)
The interrelationship of the rural-urban between Deli Serdang Regency and Medan City which are two-way and mutually beneficial can have a big impact on economic activities in both rural and urban areas so that it will improve the welfare of the people in the border areas of Deli Serdang Regency. This study aims to analyze the differences in people's income before and after working in the City of Medan, and the factors that people interact with in the city of Medan. The research method used is the average difference test and descriptive analysis. The results showed that people's income after working in the City of Medan had a higher income than before working in the City of Medan. The factor of people interacting with Medan City is dominantly influenced by jobs that produce higher salaries/wages in Medan City, better education and health facilities and services in Medan City.